Pendampingan Maharah Kalam dalam Pelajaran Sorof di FORMASPI Junior Putri Pondok Pesantren Assunniyyah Kencong Jember - Ghofur, M Abdul; Fadilah, Azizatun Nur (INAIFAS Press, 2024)
The skill of speaking Arabic at the Assunniyyah Islamic Boarding School in Kencong Jember is less popular with some students, one of which is the junior female formaspi, the problem is the lack of mastery of maharah kalam because they think that learning Arabic is very difficult and there needs to be a habit so that students can easily get used to maharah kalam, in learning Arabic as well. language layout is required and must also be able to arrange words according to well-organized grammar. Mentoring aims to provide services for junior female Islamic boarding school assunniyah students to increase maharah kalam through nahwu and sorof. The methods used to achieve the expected outcomes are divided into three elements, namely: preparation, implementation and evaluation. The results of this assistance are that female junior students have slightly improved regarding maharah kalam through sorof learning.